Mapping the performance of PV modules, effects of module type and data averaging - Huld, Thomas; Gottschalg, Ralph; Beyer, Hans Georg; Topič, Marko (Solar energy, 2010)
A method is presented for estimating the energy yield of photovoltaic (PV) modules at arbitrary locations in a large geographical area. The method applies a mathematical model for the energy performance of PV modules as a function of in-plane irradiance and module temperature and combines this with solar irradiation estimates from satellite data and ambient temperature values from ground station measurements. The method is applied to three different PV technologies: crystalline silicon, CuInSe 2 and CdTe based thin-film technology in order to map their performance in fixed installations across most of Europe and to identify and quantify regional performance factors. It is found that there is a clear technology dependence of the geographical variation in PV performance. It is also shown that using long-term average values of irradiance and temperature leads to a systematic positive bias in the results of up to 3%. It is suggested to use joint probability density functions of temperature and irradiance to overcome this bias.